Beach road : a novel - Patterson, James; De Jonge, Peter (New York : Little, Brown and Company, 2006)
A struggling Montauk lawyer agrees to defend a local man accused of murdering several flashy Hamptons types and finds himself in the midst of another trial of the century.
Keywords: Attorney and client -- Fiction; Suspense fiction